English Students' Teaching Experience Joining AIESEC Exchange Program in Practicing Teacher Competences : A Case Study of Exchange Participants Aiesec in Untan 2018-2019 - Murtianda, Ghea; Apriliaswati, Rahayu; Sumarni; Susilawati, Endang; Rosnija, Eni (Kirana Publisher (KNPub), 2023)
This research aimed to describe the experience of the exchange participants in practicing their teaching competencies through practical experience and teaching abroad. This study used qualitative research. The data were collected using a questionnaire and continued by interview. There were three exchange participants from the English Education batch 2015 and 2016 students in this research. They went to Malaysia in 2018-2019 and did a teaching project in one of the AIESEC programs called Global Volunteer. The result of the study showed that the exchange participants' experiences were relevant to practicing teaching skills. Therefore, the Global Volunteer program could be a place for English Students who want to practice their English skills and teaching competencies